A discourse analysis of stock market news In english and vietnamese (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
A Discourse Analysis of Stock Market News in English and Vietnamese is a study of how stock market news is structured and which linguistic features are typical in this news genre. This analysis focuses on exploiting four aspects: the layout, syntactic features, lexical features and cohesive devices and making comparison to find out the similarities and differences of these features between two languages. To reach these goals, 200 samples of stock market news (100 in English and 100 in Vietnamese) were collected from popular online newspapers and then analyzed based on a variety of methods, namely qualitative, quantitative, statistics, descriptive, analytic, synthetic, comparative, contrastive and inductive. The findings showed that English and Vietnamese stock market news were displayed in a common layout including summary and development. Syntactically, sentence types, comparison constructions and voice were prominent features which were thoroughly analyzed and compared. Additionally, words denoting decrease and increase, time expressions, economic terms and acronyms were typical expressions employed in both English and Vietnamese stock market news of which the economic terms in English news were more diversified than those in Vietnamese ones. Finally, with regard to cohesion, the result showed that lexical reiteration was the most frequently used which was followed by reference. Hopefully, the result of the study can be somewhat beneficial for teaching and learning English. Also, this study may be useful for journalism students in writing such type of news.